(untitled) (American Journal of Islam and Society, 1998)
Susan Strange (1996) The Retreat of the State: The Drfision of Power in the World Economy. New York, Ny: Cambridge University Press. 218 pages. 16.95 paperback. Martin J. Beck Matustik (1998) Specters of Liberation: Great ReMals in the New World Order Albany, Ny: State University of New York Press. 360 pages. 23.95 paperback. In 1996, Philip Cerny wrote in the International Journal that globalization literature is a set of contested stories that frame the categories and concepts informing public debate. Retreat and Specters tell such stories to shape perceptions of globalization as a threat demanding vigorous scholarly attention and creative political responses. Both books depict globalization as a frightening menace heralding social tumult; dislocation; “a yawning hole of non-authority” (Strange, p. 14); and a terrifying legacy of “economic immiseration, political oppression, cultural marginalization, and racial and ethnic cleansing” (Matustik, p. x). Strange outlines potential threats, leaving readers to conjure responses. Matustik seeks to open the conceptual space necessary to craft alternative conditions, leaving readers to specify the threats and imagine how to achieve alternatives. Neither author explains or analyzes globalization. Strange disdains globalization as no more than empty jargon, and describes it as an economic and technological phenomenon with political consequences. Matustik considers it to be social with political and cultural consequences. Both authors address prevailing stories of globalization as much as global conditions. Each exhorts readers to confront globalization by exploring the gritty reality and actual conditions confronting individuals, rather than by accepting prevailing stories. Thus, each confirms Cerny’s claim (1996:260) that globalization is more significant as a contested discourse than as an analytical literature or global condition. In this light, one does well to read Strange and Matustik as storytellers and to ask if their interpretive tales reflect one’s experiences and impressions of global life. Unsurprisingly, both authors tell only partial tales, but each poses worthy questions ...